A Note on Eulerian Polynomials - D. S. Kim; T. Kim; W. J. Kim; D. V. Dolgy (Abstract and Applied Analysis)
We study Genocchi, Euler, and tangent numbers. From those numbers we derive some identities on Eulerian polynomials in connection with Genocchi and tangent numbers.